DEVELOPING MOBILE BANKING SERVICES TO ENHANCE BANKING COMPETITIVENESS - Huda, Nazara Nurul; Johannes; Fitriaty (Management Department, Faculty of Economics and Business, Universitas Jambi, 2025)
This study aims to analyze the impact of mobile banking service on customer satisfaction and loyalty at Bank Jambi. A quantitative research approach was employed, with data collected through questionnaires distributed to 88 respondents who utilize mobile banking services via Google Forms. Data analysis was conducted using the Partial Least Squares (PLS) technique, revealing that service quality positively and significantly influences customer satisfaction. The result shows that the higher the level of service quality provided, the greater the customer satisfaction experienced. Additionally, customer satisfaction significantly influences customer loyalty, as satisfied customers tend to exhibit higher loyalty and recommend the bank's products and services to others. This study also found that service quality positively affects customer loyalty through customer satisfaction as a mediating factor. These findings highlight the critical role of service quality in fostering customer satisfaction and loyalty. Consequently, this study contributes to the understanding of service quality and assists in enhancing the bank's competitiveness. Improving service quality will not only increase customer satisfaction but also strengthen loyalty.